1894
DOI: 10.1098/rstb.1894.0014
|View full text |Cite
|
Sign up to set email alerts
|

The effect produced upon respiration by faradic excitation of the cerebrum in the monkey, dog, cat, and rabbit

Abstract: The object of the following investigation was to elucidate the character of representation of respiration in the highest nerve centres. For this purpose excitation method was employed, so that the results of the research are embodied the effects produced on the movements of respiration when various regions of tie cerebral hemisphere are excited. By a careful regulation of the anaesthetic state in the species of animal used, by recognition of the exact spot excited, and by employing a suitable stimulus, a const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1939
1939
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The mPFC has long been implicated in the higher-order regulation of autonomic function (Spencer, 1894;Howell and Austin, 1900;Jackson, 1931), and more recent evidence supports a privileged role for IL in this regard (for review, see Neafsey, 1990). The IL projects to brainstem cell groups involved in central autonomic control, including the nucleus of the solitary tract (NTS), the principal central terminus of interoceptive inputs carried by the vagus and glossopharyngeal nerves (Saper, 1982;Terreberry and Neafsey, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The mPFC has long been implicated in the higher-order regulation of autonomic function (Spencer, 1894;Howell and Austin, 1900;Jackson, 1931), and more recent evidence supports a privileged role for IL in this regard (for review, see Neafsey, 1990). The IL projects to brainstem cell groups involved in central autonomic control, including the nucleus of the solitary tract (NTS), the principal central terminus of interoceptive inputs carried by the vagus and glossopharyngeal nerves (Saper, 1982;Terreberry and Neafsey, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Orbitoamygdaloid and orbitohypothalamic connections as revealed in this study may, in part, provide an anatomical substrate for orbitocortically induced autonomic influences (Spencer, 1894;Smith, '38;Bailey and Sweet, '40;Sachs et al, '49;Kaada, '51;Hess et al, '52). It has also been suggested that orbitoamygdaloid projections may be involved in the mediation of trans-cortical sensory inflow of various modalities to the amygdaloid complex (Dell and Olson,'51;Dell,'52;Machne and Segundo,'56;Sawa and Delgado,'63;Valverde,'65;Hirata,'65).…”
Section: Discussionmentioning
confidence: 83%
“…It is by no means the entire neural mechanism of respiratory control for it neglects known cortical (Spencer, 1894) , hypothalamic (Ranson and Magoun, '39), and other supramedullary regions (Martin and Booker, 1879) of respiratory regulation. Furthermore it disregards known control through peripheral chemoreceptors and the various afferent pathways from viscera and periphery.…”
Section: Resultsmentioning
confidence: 98%